2019
DOI: 10.1152/ajpregu.00396.2018
|View full text |Cite
|
Sign up to set email alerts
|

How does homeostasis happen? Integrative physiological, systems biological, and evolutionary perspectives

Abstract: Homeostasis is a founding principle of integrative physiology. In current systems biology, however, homeostasis seems almost invisible. Is homeostasis a key goal driving body processes, or is it an emergent mechanistic fact? In this perspective piece, I propose that the integrative physiological and systems biological viewpoints about homeostasis reflect different epistemologies, different philosophies of knowledge. Integrative physiology is concept driven. It attempts to explain biological phenomena by contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 154 publications
0
37
0
1
Order By: Relevance
“…The term “homeostasis” refers to the stability of the body’s “inner world.” In systems biology, homeostasis is an emergent phenomenon, but in integrative physiology homeostasis is a goal—it is the goal [ 71 ]. Thus, Claude Bernard, the founding father of integrative physiology, wrote, “The constancy of the internal environment is the condition for free and independent life…All the vital mechanisms, however varied they might be, always have one purpose, that of maintaining the integrity of the conditions of life within the internal environment” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The term “homeostasis” refers to the stability of the body’s “inner world.” In systems biology, homeostasis is an emergent phenomenon, but in integrative physiology homeostasis is a goal—it is the goal [ 71 ]. Thus, Claude Bernard, the founding father of integrative physiology, wrote, “The constancy of the internal environment is the condition for free and independent life…All the vital mechanisms, however varied they might be, always have one purpose, that of maintaining the integrity of the conditions of life within the internal environment” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to this principle, physiological variables are regulated and maintained at their normal values thanks to negative feedback regulatory loops. Today, complexity challenges the homeostatic view on the cardiovascular system [ 1 , 2 , 3 ]. We recently demonstrated that at least part of this complexity is explained by the self-organization of a cardiovascular system poised at criticality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is of course a coarse approximation because it is implicit that the different subsystems must interact in order to assure a system-wide homeostatic state, remaining outside the scope of the reductionist approach to physiology. Systems biology, on the other hand, suggests that systemic homeostasis “emerges” from an underlying network and interactions between variables that span the whole system ( Goldstein, 2019 ). Figures 7–9 show 6 distinct clusters, where the intra-cluster interactions between related variables may well represent the textbook examples of local subsystem homeostasis, whereas the inter-cluster interactions between very distinct variables most probably convey new and unexplored information of how homeostasis is established at the system level in the optimal conditions of youth and health, and how the loss of homeostasis arises with aging and/or disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the associations between parameters are present even for healthy values and represent a continuum. From the systems biology perspective, the network structure is a direct result of the coordination, or lack thereof, of components that are linked by homeostatic feedback ( Goldstein, 2019 ). For example, in a simple negative feedback a change in a regulated variable is detected by a comparator in the organism that through effector variables counteracts the perturbation ( Fossion et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%